Military expenditure and economic activity : the Colombian case (2003)
We enhance a standard RBC model to account for military expenditure and the costs of an internal conflict or war. The model captures the natural trade-off in military expenditure: crowding out of private consumption and investment but less destruction (and, therefore, higher marginal productivity) of private capital (and labor). Hence, military expenditure below (above) a certain threshold generates a positive (negative) net benefit in terms of output. The model is calibrated to an annual frequency using Colombian data. We find that an increase in military expenditure of 1 % GDP (the current policy of Colombian authorities) increases investment and output above the steady state during several periods, before the shock fades away. Even though consumption falls on impact (to open up space for the additional military expenditure and private investment), it increases above its stationary trend after three periods, remains on positive grounds thereafter, and the cumulated net gain is positive.